The Effect of Supply Chain and Consumer Preferences on the Formation of Economic Model - Maloletko, Alexander; Volkov, Daniil; Vishnyakova, Victoria; Shatsky, Alexander (International Journal of Supply Chain Management, 2018)
Abstract – Technologies of marketing evolve over time. This phenomenon is due to the need to ensure the concept of marginal utility, called the mainstream, and the possible leveling of market failures in the classical sense. The development of the theoretical sections of the economy allows us to form a model of paradigm in thinking of the society. The complex of measures for the promotion of goods is transformed into a universal mechanism of the market, which forms consumer preferences, volume of consumer choice and supply chain, which is reflected in this research. The influence of behavioral Economic development in the key of innovative marketing technologies is also considered.